On species of Anisodactylus of the Russian Far East, with a description of a new species and the first record of A. tricuspidatus for Russia (Coleoptera: Carabidae: Harpalini) - Kataev, Boris M.; Makarov, Kirill V.; Sundukov, Yurii N. (Zootaxa, 2024)
A review of the ground beetle genus Anisodactylus Dejean, 1829 of the Russian Far East is given. The fauna of this region includes four species of two subgenera: A. (Pseudanisodactylus) signatus (Panzer, 1796), A. (P.) punctatipennis Morawitz, 1862, A. (Anisodactylus) tricuspidatus Morawitz, 1863 and A. (A.) arsenjevi sp. nov. The latter species is described from several localities in the southern Primorye Territory (type locality: 1 km S Beltsovo Village, Arsenjevka River floodplain, Yakovlevka District); it is rather distinct among the Palaearctic species and most similar in general habitus to some Nearctic species, especially to A. (A.) harrisii LeConte, 1863. Anisodactylus (A.) tricuspidatus is recorded for Russia for the first time. A lectotype of A. punctatipennis is designated. The distribution and distinctive characters of all four species are discussed, and a key for their determination is provided; their habitus and male and female genitalia are illustrated.